Experience with the Crescent® cannula for adult respiratory VV ECMO: a case series. (November 2022) - Fleet, Daniel; Morris, Idunn; Faulkner, Gail; Harvey, Chris
Introduction: The Crescent ® is a recently introduced dual lumen cannula by which veno-venous extracorporeal membrane oxygenation (VV ECMO) is delivered. It has a number of features that enhance its ease of placement, pressure-flow dynamics and may reduce catheter-related complication rates. Methods: We present the first case series of its kind analysing this device by means of a retrospective observational study of prospectively collected data from the first year of its use in a high volume severe acute respiratory failure centre (Glenfield, UK). We compare complication rates of the Crescent ®, with data from the international ELSO database and our own historic centre data and discuss subjective clinician experience of introducing this device. Results: Over the first 12 months of its use (23/09/2019–23/09/2020), 54 patients were cannulated using a Crescent ® catheter. There were no serious/life-threatening adverse events and a low number of minor cannula-related complications. Subjectively users found it has a number of advantages over other devices and configurations, not captured within current data collection frameworks. Conclusion: The Crescent ® is a safe and effective device by which to deliver VV ECMO support to patients with severe acute respiratory failure.